Electrochemical Glucose Sensor Based on Dual Redox Mediators - Changyun Quan; Yue Zhang; Yuanyuan Liu; Liping Wen; Haixia Yang; Xueqin Huang; Minghui Yang; Binjie Xu (Biosensors)
Electrochemical glucose sensor holds significant promise for the monitoring of blood glucose levels in diabetic patients. In this study, we proposed a novel electrochemical glucose sensor based on 1,10-Phenanthroline-5,6-dione (PD)/Ru(III) as a dual redox mediator. The synergistic effect of PD and Ru(III) was utilized to efficiently facilitate the electron transfer between the enzyme-active center and the electrode. Then, a commercial disposable electrochemical glucose sensor was constructed based on screen-printing electrodes. Experimental results indicated the synergy between PD and Ru(III) provided a promising electron transfer environment for a glucose dehydrogenase (GDH)-catalyzed glucose reaction. The sensor exhibits a linear glucose response range from 0.01 to 38.6 mmol/L, with a limit of detection (LOD) as low as 7.0 µmol/L and a sensitivity of 38 µA·L/(mmol·cm2). The accuracy of the sensor was further validated in spiked recovery tests of human venous blood samples. The glucose recovery rate was between 99.5% and 107%, with a relative standard deviation (RSD) of less than 3.2%. These results demonstrate that our sensor has high potential for commercialization and practical application in glucose monitoring.